Geopolitik dan nasionalisme: Membangun kesadaran warga negara dalam menjaga kedaulatan NKRI - Khoiruddin, Muhammad Ikhwan (Maliki Interdisciplinary Journal, 2025)
The strategic roles of geopolitics and nationalism in building citizen awareness to safeguard the sovereignty of the Republic of Indonesia (NKRI). The main issue addressed is the weak geopolitical awareness amid globalization, transnational ideologies, and non-traditional threats such as information warfare. Using a descriptive-qualitative approach, this study analyzes how education, religious figures, digital media, and religious organizations shape inclusive geopolitical understanding and contextual nationalism. It also compares various countries’ strategies in fostering nationalism and responding to global challenges. The findings reveal that strengthening national identity, improving digital literacy, and integrating Pancasila values into education and public policy are key solutions to reinforce national resilience. In conclusion, synergy among the education, religious, media, and government sectors is essential to instill geopolitical awareness and nationalism as the foundation of NKRI's resilience in the global era.